Cyclic GMP-AMP as an Endogenous Second Messenger in Innate Immune Signaling by Cytosolic DNA - Kato, Kazuki; Omura, Hiroki; Ishitani, Ryuichiro; Nureki, Osamu (Annual review of biochemistry, 2017)
The innate immune system functions as the first line of defense against invading bacteria and viruses. In this context, the cGAS/STING [cyclic guanosine monophosphate (GMP)-adenosine monophosphate (AMP) synthase/STING] signaling axis perceives the nonself DNA associated with bacterial and viral infections, as well as the leakage of self DNA by cellular dysfunction and stresses, to elicit the host's immune responses. In this pathway, the noncanonical cyclic dinucleotide 2',3'-cyclic GMP-AMP (2',3'-cGAMP) functions as a second messenger for signal transduction: 2',3'-cGAMP is produced by the enzyme cGAS upon its recognition of double-stranded DNA, and then the 2',3'-cGAMP is recognized by the receptor STING to induce the phosphorylation of downstream factors, including TBK1 (TANK binding kinase 1) and IRF3 (interferon regulatory factor 3). Numerous crystal structures of the components of this cGAS/STING signaling axis have been reported and these clarify the structural basis for their signal transduction mechanisms. In this review, we summarize recent progress made in the structural dissection of this signaling pathway and indicate possible directions of forthcoming research.